(untitled) (Journal of Medicine, 2008)
The use of radioiodine-131 for the treatment of hyperthyroidism is a very simple and cheap form of therapy and highly effective and is now the predominant definitive therapy both as primary treatment and following relapse after anti thyroid drugs. This study was carried out in Khulna medical college from January 2002 to January 2003 to assess the degree of effectiveness of radioiodine therapy in case of hyperthyroidism. This was a prospective study of 50 patients with hyperthyroidism (28 female, 22 male, mean age 39.87 years) treated with radioiodine-131 and followed up for a period of one year. The dose of radioiodine-131 ranged from 7-10 mci. Out of 50 patients 38 (76%) were found to have diffuse toxic goitre, 5(10%) have solitary toxic nodule 1(2%) have multi nodular toxic goitre, 4(8%) have impalpable gland with thyrotoxicosis and 2(4%) with relapsing thyrotoxicosis received oral radioiodine therapy. Serum T3 was elevated in 43(86%) and was normal in 7(14%) cases. Serum T4 was normal in 4 (8%) cases that were T3 thyrotoxicosis and rose in 46(92%) cases. Serum TSH was reduced in all cases. Thyroid scan shows warm/ diffuse uptake in 44 (88%) and hot nodule in 6(12%) cases. Post therapy clinical and biochemical evaluation of thyroid function was done at 3 months, 6 months, 9 months and 12 months interval. The patient was classified as cured if the biochemical status was either euthyroid or hypothyroid at one year without further treatment by antithyroid drugs or radioiodine. The incidence of euthyroid, hypothyroidism and hyperthyroidism within one year was 60.00%, 35.60% and 4.40% and the cure rate was 95.6%. From this study we found that radioiodine-131 therapy is a simple, safe and effective means to normalize thyroid function status in patients with hyperthyroidism. Â DOI = 10.3329/jom.v9i1.1422 Â J MEDICINE 2008; 9 : 27-30